Zoom Exhaustion & Fatigue Scale - G. Fauville (Elsevier, 2021)
In 2020, video conferencing went from a novelty to a necessity, and usage skyrocketed due to shelter-in-place throughout the world. However, there is a scarcity of academic research on the psychological effects and mechanisms of video conferencing, and scholars need tools to understand this drastically scaled usage. The current paper presents the development and validation of the Zoom Exhaustion & Fatigue Scale (ZEF Scale). In one qualitative study, we developed a set of interview prompts based on previous work on media use. Those interviews resulted in the creation of 49 survey items that spanned several dimensions. We administered those items in a survey of 395 respondents and used factor analyses to reduce the number of items from 49 to 15, revealing five dimensions of fatigue: general, social, emotional, visual, and motivational fatigue. Finally, in a scale validation study based on 2724 respondents, we showed the reliability of the overall scale and the five factors and demonstrated scale validity in two ways. First, frequency, duration, and burstiness of Zoom meetings were associated with a higher level of fatigue. Second, fatigue was associated with negative attitudes towards the Zoom meetings. We discuss future directions for validation and expansion of the scale.